Shared Adversity Increases Team Creativity Through Fostering Supportive Interaction - Bastian, Brock; Jetten, Jolanda; Thai, Hannibal A.; Steffens, Niklas K. (Frontiers in Psychology, 2018)
In the current era, building more innovative teams is key to organizational success, yet there is little consensus on how best to achieve this. Common wisdom suggests that positive reinforcement through shared positive rewards builds social support within teams, and in turn facilitates innovation. Research on basic group processes, cultural rituals, and the evolution of pro-group behavior has, however, revealed that sharing adverse experiences is an alternative path to promoting group bonding. Here, we examined whether sharing an adverse experience not only builds social support within teams, but also in turn enhances creativity within novel teams. Drawing on behavioral observation of an experimental group interaction we find evidence that sharing an adverse (vs. non-adverse) experience leads to increased supportive interactions between team members and this in turn boosts creativity within a novel team. These effects were robust across different indicators of creativity: objective measures of creativity, third party ratings of the creativity of group products, and participants’ own perceptions of group creativity. Our findings offer a new perspective from which to understand how best to boost innovation and creative output within teams.